Anastrozole monotherapy further improves near-adult height after the initial combined treatment with leuprorelin and anastrozole in early-maturing girls with compromised growth prediction: results from the second phase of the GAIL study - Papadimitriou, Dimitrios T.; Dermitzaki, Eleni; Christopoulos, Panagiotis; Livadas, Sarantis; Grivea, Ioanna N.; Mastorakos, George (Frontiers in Endocrinology, 2024)
Background. The first phase of the GAIL study (Girls treated with an Aromatase Inhibitor and Leuprorelin, ISRCTN11469487) has shown the combination of anastrozole to with leuprorelin for 24m being safe and effective in improving predicted adult height (PAH) in girls with early puberty and compromised growth prediction by +1.21 SDS (+7.51 cm) compared to inhibition of puberty alone +0.31 SDS ( +1.92cm). Objectives and Hypotheses. In the second phase of the GAIL study, we assessed the adult height/near adult height (NAH) at the end of the first phase, and additionally the efficacy of anastrozole monotherapy thereafter in further improving NAH. Methods. We measured AH (age 16.5 yrs)/NAH [bone age (BA) 15 yrs] of the 40 girls included, divided in two matched groups: Group A (20 on anastrozole + leuprorelin) and Group B (20 on leuprorelin alone). Group A was further randomized into two subgroups. Group A1 (n=10), after completion of the combined therapy, received anastrozole monotherapy 1 mg/day until BA 14yrs with a 6-month follow-up. Group A2 (n=10) and B (n=20), that had received only the combined treatment and leuprorelin alone respectively, were recalled for AH/NAH evaluation. Results. AH/NAH exceeded the PAH at the completion of the 2-year initial phase of the GAIL study in all groups but the result was statistically significant only in Group A1: NAH-PAH Group A1: +3.85 cm (+0.62 SDS) p=0.01, Group A2: +1.6 cm (+0.26 SDS) p=0.26, Group B: +1.7 cm (+0.3 SDS) p=0.08. The gain in Group A1 was significantly superior to that of Group A2 (p=0.04) and Group B (p=0.03). Anastrozole was safe even as monotherapy in Group A1. Conclusions. In early maturing girls with compromised growth potential the combined treatment with leuprorelin and anastrozole for 2yrs or until the age of 11yrs resulted in a total gain in height of +9.7 cm when continuing anastrozole monotherapy until attainment of NAH, compared to +7.4 cm if they do not continue with the anastrozole monotherapy and +3.6 cm when treated with leuprorelin alone. Thus, the combined intervention ends in the shortest distance from target height if continued with anastrozole monotherapy until BA 14 years.